Nano-montmorillonite modified foamed paste with a high volume fly ash binder. Issue 16 (3rd February 2017) - Li, Zhipeng; Gong, Jing; Du, Sen; Wu, Jianlin; Li, Jianfen; Hoffman, Daniel; Shi, Xianming
Abstract : This study demonstrated a nanoclay-modified HVFA foamed paste as a thermal insulation material and obtained an in-depth understanding of its hydration mechanism. Abstract : This laboratory study explores a cost-effective and environmental friendly foamed paste with satisfactory physical properties and outstanding thermal insulation properties. Such a composite material was made by using a high volume of class F coal fly ash as a replacement of Portland cement (70% by mass) and nano-montmorillonite as an admixture. Replacing cement with fly ash at high levels is environmentally and economically desirable, as this not only reduces the energy and carbon footprint of the foamed paste, but also diverts the coal fly ash from the waste stream. A statistical design of experiments was adopted and executed to investigate the effects of various factors on the properties of the composite. At the age of 28 days, the pastes exhibited a high compressive strength ranging from 1.77 MPa to 6.51 MPa and a low thermal conductivity in the range of 0.071 W (m −1 K −1 ) to 0.173 W (m −1 K −1 ). Two foamed mixes were chosen for further investigation as they presented the best and worst performance as a thermal insulation material. The scanning electron microscopy shed light on the best foamed mix, which contains 70% fly ash, 30% cement, and 1% nano-montmorillonite, and how its microstructure differed from that of the worst mix without nano-montmorillonite. The Ca content, Si/Ca ratio and Al/Ca ratio were obtained from energy-dispersive X-ray spectroscopy of hardened samples, and used to help explain the observed strength difference between these two mixes. X-ray diffraction was also employed to elucidate the hydration mechanism of HVFC foamed paste.